Tramway obstacles detection based on information fusion of MMV radar and machine vision - Guang-yao ZHAI; Rong CHEN; Jian-feng ZHANG; Ji-guang ZHANG; Cheng WU; Yi-ming WANG (物联网学报)
A method of obstacle detection based on information fusion of millimeter wave radar and machine vision sensor was proposed.Firstly,the millimeter wave radar and camera calibration,image and radar realize spatiotemporal data synchronization,the target position was accurate projection detected by radar images,and then a method of generating radar target region of interest,and the image information using the frame difference method,image detection of moving objects,detection area was put forward.Finally,the radar detection area was compared with the machine vision detection area.The coincidence degree was calculated,and the target was divided into pedestrian or vehicle according to coincidence degree.The experimental results show that the method can detect the obstacle of millimeter wave radar and machine vision well,and make up for the shortage of single sensor in obstacle detection.